-3(9y+3)+9y=-19y

Simple and best practice solution for -3(9y+3)+9y=-19y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(9y+3)+9y=-19y equation:



-3(9y+3)+9y=-19y
We move all terms to the left:
-3(9y+3)+9y-(-19y)=0
We add all the numbers together, and all the variables
9y-3(9y+3)-(-19y)=0
We multiply parentheses
9y-27y-(-19y)-9=0
We get rid of parentheses
9y-27y+19y-9=0
We add all the numbers together, and all the variables
y-9=0
We move all terms containing y to the left, all other terms to the right
y=9

See similar equations:

| -14-14k=-7(2k+2) | | -10-g=-3g-10+2g | | 11d-10-2d=9d-10 | | 9z+3=-3(-3z-1) | | -u+17=17-8u+7u | | 9(3v-12)=18+20v | | 3(-2q+18)-6=-2q | | 6c+14c-17=15+18c | | -11-7w=-11-19w+12w | | 20-4q=-16-19q+19q | | 17n-5-4n=13n+17 | | 7x2-3x-1=0 | | -17+19s=6s+12+13s | | 19-10z=z-7-13z | | g-5=9-g | | 2x+8/4x-5=3 | | 2x=79000+(x/40) | | 8=〖(7x+2)〗^2-28x | | 1/2-8c=-15/2 | | x*2+10=74 | | 18,62x-3=15,57x+3,83 | | 2x+54=6 | | x*2-9=7 | | x⁴+8x³-x²-68x+60=0 | | x²+8×-10=0 | | 2x*2-4x+6=18 | | 9x+2^(4x-1)=49 | | 3x+1+x-5=90 | | 6x^=-42x | | 3x^-6x+15=0 | | (x^2-4x-12)(x^2+x-12)=0 | | 3k^2+k+4=0 |

Equations solver categories